Elucidating Genomic Instability and its Outcomes as Cancer Origin (International Journal of Research in Pharmaceutical Sciences and Technology, 2022)
Increased propensity of alterations in the genome during the life cycle of cells is called as genomic instability. It is a major cause of oncogenesis. There are four major mechanisms that control the genome instability while the normal cells divide. These mechanisms are DNA replication of high precision and accuracy in S-phase, mitosis involving precise chromosome separation, correct repair of infrequently occurring DNA damage, and cell cycle development in synchronized manner. This briefly throws light on processes at molecular level that play significant role in preventing oncogenesis through genomic instability.